(untitled) (Journal of Preventive and Social Medicine, 2025)
Background: The garment industry is Bangladesh’s largest source of employment and its top export earner. The research aims to identifying workplace and other factors influencing job satisfaction of female garments workers in Bangladesh. Methods: The study used a cross-sectional design conducted over a twelve-month period, from January 1, 2019 to December 31, 2019 focusing on female garment workers in a garment factory located in Gazipur. Participants were selected conveniently, based on their involvement in the different sections of garment and their willingness to participate. The sample size consisted of 307 respondents. Data were collected using a semi-structured questionnaire that gathered information on socio-demographic characteristics and identified workplace and other factors influencing job satisfaction. Results: All of the respondents were female, their mean age was 29.73±7.19 years, mostly were married (84%), and less than half (45.3%) had primary education. The mean of monthly family and personal incomes of the respondents were Tk.17,639.41±4,292.70 and Tk. 9,047.66±768.71 respectively. Among the respondents, 39.1% belonged to packing section, and had been in the employment for 4.83±2.51 years. All the respondents worked 8 hours/day for 6 days and their average over time per day was about 2 hours. Among the different sociodemographic and work-related variables the satisfaction scores were found to be influenced by age, monthly personal income, duration of employment, and working section. Binary logistic regression indicated that for every additional unit of duration of employment respondents were 1.15 times more likely to develop higher satisfaction and workers of cutting section were 2.53 times more likely to have high job satisfaction. Conclusion: Measures need to be taken to alleviate those factors prohibiting high job satisfaction in the garment sectors to promote the female workers in greater contribution in their profession. JOPSOM 2024; 43(1): 50-58